Upaya Edukasi Kesehatan Reproduksi Kepada Anak Usia Remaja Di Sekolah Menengah Atas Swasta Army Putra Makassar - Ani; Sudirman (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Reproductive health is a condition in which a person is physically and mentally and socially healthy which is directly related to the reproductive process in adolescent girls or boys. Knowledge related to reproductive health in adolescents at an early age is very useful to prevent free sex behavior. This service activity has been carried out for 2 days from 18 to 19 October 2021 for 89 participants. a total duration of 8 hours, held at SMAS Army Putra Makassar. Teenagers have a very high curiosity about their reproductive health and teenage students are enthusiastic about receiving reproductive health materials, the topics most teenagers want to know are related; various diseases that can attack the reproductive organs, how to take care of the cleanliness of intimate organs, sexual problems and how to prevent free sex behavior. Most of the teenage students of SMAS Army Putra Makassar have received educational materials related to reproductive health but still need assistance regarding reproductive health.